As contribuições da Unipampa no desenvolvimento da saúde em Uruguaiana /RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The universities are fundamental in the process of building society, as they are capable of understanding local needs and modifying the scenarios of the regions where they are implemented. Especially in an underdeveloped and continental country like Brazil, with different and unequal local realities, this situation can be seen in the southern half of the state of Rio Grande do Sul, historically diagnosed by its declining economy. As a measure to modify the scenarios of poorer regions, the federal government instituted the plan for Restructuring and Expansion of Federal Universities. From this program, in 2006, the Federal University of Pampa was established to meet the demands of ten cities in the region, differentiating them in courses and areas of concentration. Thus, courses in the health area were concentrated on the Uruguaiana campus. Therefore, the insertion of Unipampa in the region was looking for a change in the local scenario in favor of development. This study seeks to analyze the role of the Federal University of Pampa, Uruguaiana campus, in the development of local healthcare. Specifically, it aims to: a) Describe the teaching, research, and extension activities developed; b) Find out the perception of development agents regarding the university's actions in favor of the municipality's healthcare; c) present the contributions of the Uruguaiana campus to the development of local healthcare. Methodologically, the research has a mixed approach and is characterized as exploratory-descriptive, conducted through a case study. The data collection techniques used were documentary research and semi-structured interviews. The document collection stage took place in consultations of documents available at the university, in the municipal, state and federal governments as well as partner institutions. Subsequently, 13 semi-structured interviews were conducted with healthcare development agents. The data from the documentary research and interviews were analyzed using the content analysis of Bardin (2016), while the quantitative data obtained from documents underwent descriptive statistical treatment. Finally, the data were triangulated to describe the phenomenon under study. The results demonstrate that the establishment of Unipampa contributed to the premises of local development, modifying the previous scenario. The documentary research revealed a new landscape of research in the municipality's healthcare sector, with professors and students actively involved in the healthcare system, increasing the number of services provided to the local community. Additionally, there was evident interaction with the population, particularly in research and extension projects, with over 1500 activities being carried out during the research period. The interviews revealed the significance of Unipampa, to the point that healthcare development agents considered it indispensable for the health of Uruguaiana, highlighting its participation in the evolution of the functioning of the HSCU. Furthermore, Unipampa provided the population with a larger amount of atendence services in health, access to technology, and protocols that were previously unavailable to the local population, prompting the healthcare system to undergo continuous updates. These findings, along with other evidence, are presented throughout the study, including the weaknesses of this interaction, such as the lack of institutionalization of Unipampa's involvement.
Unipampa's contributions to health development in Uruguaiana/RS
Keywords: universidade; saúde; desenvolvimento local; university; health; local development; CNPQ::CIENCIAS SOCIAIS APLICADAS